Flechas e martelos: Marx e Engels como leitores de Lewis Morgan - Lucas Parreira Álvares (2019)
The dissertation “Arrows and Hammers: Marx and Engels as Readers of Lewis Morgan” is an investigation based on an immanent analysis that aims to apprehend the nexus of three works that compose the “plot” that motivated this work: the classic Ancient Society, the American Lewis Morgan, who consecrated his name as one of the most important anthropologists of the nineteenth century; the so-called Karl Marx Ethnological Notebooks, which form a set of drafts that the author developed in the final years of his life, among them, of the aforementioned work of Morgan; and Friedrich Engels's Origin of the Family, Private Property, and State, a work that he developed both from Marx's drafts and from the original work of Morgan. Marx died shortly after having drafted Morgan's work. His death would have interrupted, according to Engels, the author's plans to expose the discoveries and novelties introduced by Morgan about the earliest social forms that preceded the capitalist mode of production. Thus, the publication of The Origin by Engels would have been, according to its author, "the execution of a will". With the publication of these Marx Papers in 1972, that is, almost 100 years after the plot that articulated these three authors (between 1877 and 1884), we finally have elements to compare the specificities between the readings that Marx and Engels made of Lewis Morgan, identifying possible similarities and highlighting the visible differences. In broad strokes, this enterprise was what motivated the production of this dissertation.